Analysis of cultural distance’s influence on intentions to visit Spain as a tourist destination - Gemar-Castillo, Germán; Soler-García, Ismael Pablo; Villar, Henar (Universidad de Algarve, 2019)
In the tourism industry, visiting tourists’ intentions have been the subject of numerous investigations for decades. However, the factors determining choices of specific tourist destinations have still not been clearly defined. The country of origin’s culture has been widely acknowledged to be a key element in variations in tourists’ behaviours. This study evaluated the capacity of cultural distance between countries of origin and Spain – as specified by Hofstede’s proposed model – to influence intentions of visiting Spain in the near future. These intentions were measured as a function of the theory of planned behaviour. The results facilitate the identification of relevant issues affecting potential tourists’ intention to visit Spain. Analyses of the data’s validity and reliability yielded satisfactory solutions that allow conclusions to be drawn about why behavioural intentions vary significantly depending on tourists’ cultural distance from Spain. The Hofstede model’s ability to explain intention to visit was, therefore, confirmed.

En el sector turístico, la intención de visita ha sido objeto de numerosas investigaciones desde hace décadas, sin embargo los factores determinantes de la elección del destino turístico no han quedado claramente definidos. La cultura del país de origen se ha reconocido como elemento clave a la hora de discernir las conductas tan variadas por las que optan las personas. En este estudio, se evalúa la capacidad de la distancia cultural entre los países de origen considerados y España, según el modelo propuesto por Hofstede, de influir en la intención de visitar nuestro país en los próximos años, medida ésta en función la Teoría del Comportamiento Planificado – y otros dos factores añadidos. La interpretación de los resultados permite identificar las cuestiones relevantes en la intención de visita de los potenciales turistas. Los análisis de validez y fiabilidad de los datos empleados arrojan soluciones satisfactorias que permiten así establecer conclusiones sobre intención conductual muy distintas en función de los niveles de distancia cultural del turista. Se confirma, por tanto, la capacidad del modelo de Hofstede de explicar la intención de visita de España.
Análisis de la influencia de la distancia cultural en la intención de visitar el destino turístico España
Keywords: Intención (Lógica); Viajes - Innovaciones tecnológicas; Hofstede’s model; Cultural distance; Intention to visit; Theory of planned behaviour